WANPRESTASI DAN AKIBATNYA DALAM PELAKSANAAN PERJANJIAN - Muhammad Riandi Nur Ridwan,; Yana Sukma Permana, (The Juris, 2022)
Agreement by the parties as a basis for the legal relationship of the agreements that have been approved, which give rise to rights and obligations of the parties. With the expected agreement all of what has been agreed to function normally, but in practice in certain circumstances the exchange of achievement does not always work as it should so that it appears what is called a default. Default is: "A situation where a debtor (debt) does not fulfill or implement the achievements as stipulated in an agreement". A person is declared in default because: Absolutely not meet achievement; achievements which are not perfect; Late meet achievement; and do what is in the agreement are forbidden to do. Default cause problems, such as: When a debtor is declared in default, what the result of a default and how efforts for settlement of default may provide protection for the parties. In order to create what is the purpose of making the agreement, needed a solution that could provide protection for the parties, especially the injured party. In order to create what is the purpose of making the agreement, needed a solution that could provide protection for the parties, especially the injured party.